Effects of bi-hemispheric anodal transcranial direct current stimulation on soccer player performance: a triple-blinded, controlled, and randomized study - Rocha, Jader Vinicius Da Silva; Almeida, Rodrigo Freire de; de Lima Cordeiro, Bárbara Naeme; Cardoso Sarcinelli, Carlos Henrique; Zimerer, Carla; Arêas, Fernando Zanela (Frontiers in Sports and Active Living, 2024)
The search for increased performance and physical performance are linked to the use of ergogenic resources. The vertical jump is one of the measures commonly used to evaluate the performance of lower limbs in athletes. Transcranial direct current stimulation (tDCS) is a non-invasive, safe, economically viable technique that can modulate cortical excitability, which can influence the increase in the performance of athletes in general. This study aimed to investigate whether the use of tDCS on the primary motor cortex (M1) improves the performance of soccer players. A cross-sectional study was conducted. Twenty-seven players were randomized into three groups: Active tDCS group (n = 9), Sham group (n = 9), and control group (n = 9). Stimulation was applied at 2 mA for 15 min using a cephalic mount. Visual Pain Scale (VAS) and Subjective Recovery Scale (SRS) were monitored before and after tDCS. In addition, the participants performed the Countermovement Jump (CMJ) before and after the stimulation intercalated with Heart Rate (HR) and Rating of Perceived Exertion (RPE CR-10). No differences were found in any of the performance variables analyzed (p > 0.05) nor in the responses of HR (p > 0.05), RPE (p > 0.05), VAS (p > 0.05), and SRS (p > 0.05) between groups. The tDCS in M1 did not change the performance of the vertical jump, and there was no improvement in the subjective scales. New studies should also be developed with different stimulus intensities in different cortical areas and sports modalities.